Content Area Literacy Strategies That Work: Do This, Not That - Wilfong, Lori G (Eye on Education, 2019)
Content area teachers are now being tasked with incorporating reading and writing instruction, but what works? In this essential book from Routledge and AMLE, author Lori G. Wilfong describes ten best practices for content area literacy and how to implement them in the middle-level classroom. She also points out practices that should be avoided, helping you figure out which ideas to ditch and which to embrace. Topics covered include: (1) Building background knowledge quickly; (2) Using specific strategies to scaffold focus while reading; (3) Using small group reading strategies to bring personal response and accountability to the content; (4) Understanding items that make reading in different disciplines unique; (5) Teaching content area vocabulary in meaningful ways; (6) Making writing an authentic process through daily and weekly assignments; and (7) Planning and teaching effective informational and argumentative pieces. Each chapter includes Common Core connections and practical templates and tools. The templates are available as free eResources so you can easily print them for classroom use. [This book was co-produced by the Association for Middle Level Education (AMLE).]